A new vole from Xizang, China and the molecular phylogeny of the genus Neodon (Cricetidae: Arvicolinae) - Liu, Shao Ying; Sun, Zhi Yu; Liu, Yang; Wang, Hao; Guo, Peng; Murphy, Robert W. (Zootaxa, 2012)
During a faunal survey in southern Xizang, we collected 27 specimens of voles that could not be identified as any knownspecies in the Arvicolinae. These specimens shared the following morphological characteristics, not corresponding withany other arvicoline species: the first lower molar possessed five closed triangles, the third upper molar exhibited eitherfour or three inner angles, and the tails of all specimens measured 30% of the body length. Their proximal baculum of theglans was very sturdy and trumpet-shaped, the distal baculum was tongue-like and sturdy, and the lateral bacula were veryshort. Molecular phylogenetic analyses based on nucleotide sequences of the mitochondrial cytochrome b (cyt b) geneclustered these specimens as a distinct lineage within the genus Neodon. According to the morphological and moleculardata, we described them as a new species, Neodon linzhiensis. Our phylogenetic analysis strongly supported that Lasio-podomys fuscus, Phaiomys leucurus, Neodon sikimensis, N. irene and the new species formed a monophyletic group, notincluding N. juldaschi. We suggested that L. fuscus and P. leucurus should be transferred to Neodon and that N. juldaschishould be removed from this genus. Following our new delineation of Neodon, we proposed a redefinition of the morphological diagnostic characters of the genus.